ANALYSIS OF ENTRANCE REGION HEAT TRANSFER IN A CONCENTRIC FINNED ANNULUS UNDER LAMINAR FLOW REGIME - Philander, Evan
Application of longitudinal fins in a concentric annulus pipe is intended to increase heat transfer surface area between the pipe surface and fluid so that higher heat transfer rate can be obtained. However, the presence of fins may affect and decrease overall heat transfer coefficient especially in the entrance region. Therefore, in this study, experimental and CFD simulation were conducted in order to evaluate the effect of number of fins to the corresponding heat transfer coefficient. Experimental and simulation results show that the heat transfer coefficient decreased with higher number of fins. In sequences, the value of heat transfer coefficient obtained from experiment at the condition of x = 60 mm and ReDh = 1200 for specimen with fin number of 15, 35, and 55 are 10.98 W/m2.K, 11.37 W/m2.K, and 9.19 W/m2.K, respectively. The values proportionally decrease with longer x or with the decrement of ReDh. Comparison with simulation results shows that Nusselt numbers obtained from the experimental study have smaller values. However, the behaviour of Nusselt number to the change of independent variables from both methods show a similar agreement. Hence, either simulation or experiment can be used to evaluate heat transfer phenomenon of a finned annulus pipe. Afterward, heat transfer characteristics obtained from this study can be represented by a correlation equation in the term of dimensionless parameters, NuDh, GzDh-1, and ????/????. The equation has Root Mean Square Error of 0.299 and 92% of the predicted values have deviation below 15% from the actual values.